CT Angiography Manual Multiplanar Vessel Diameter Measurement vs. Semiautomated Perpendicular Area Minimal Caliber Computation of Internal Carotid Artery Stenosis - Siepmann, Timo; Barlinn, Kristian; Floegel, Thomas; Barlinn, Jessica; Pallesen, Lars-Peder; Puetz, Volker; Kitzler, Hagen H. (Frontiers in Cardiovascular Medicine, 2021)
Objective: To determine the diagnostic agreement of CT angiography (CTA) manual multiplanar reformatting (MPR) stenosis diameter measurement and semiautomated perpendicular stenosis area minimal caliber computation of extracranial internal carotid artery (ICA) stenosis. Methods: We analyzed acute cerebral ischemia CTA at our tertiary stroke center in a 12-month period. Prospective NASCET-type stenosis grading for each ICA was independently performed using (1) MPR to manually determine diameters and (2) perpendicular stenosis area with minimal caliber semiautomated computation to grade luminal constriction. Corresponding to clinically relevant NASCET strata, results were grouped into severity ranges: normal, 1–49%, 50–69%, and 70–99%, and occlusion. Results: We included 647 ICA pairs from 330 patients (median age of 74 [66–80, IQR]; 38–92 years; 58% men; median NIHSS 4 [1–9, IQR]). MPR diameter and semiautomated caliber measurements resulted in stenosis grades of 0–49% in 143 vs. 93, 50–69% in 29 vs. 27, 70–99% in 6 vs. 14, and occlusion in 34 vs. 34 ICAs (p = 0.003), respectively. We found excellent reliability between repeated manual CTA assessments of one expert reader (ICC = 0.997; 95% CI, 0.993–0.999) and assessments of two expert readers (ICC = 0.972; 95% CI, 0.936–0.988). For the semiautomated vessel analysis software, both intrarater reliability and interrater reliability were similarly strong (ICC = 0.981; 95% CI, 0.952–0.992 and ICC = 0.745; 95% CI, 0.486–0.883, respectively). However, Bland–Altman analysis revealed a mean difference of 1.6% between the methods within disease range with wide 95% limits of agreement (−16.7–19.8%). This interval even increased with exclusively considered vessel pairs of stenosis ≥1% (mean 5.3%; −24.1–34.7%) or symptomatic stenosis ≥50% (mean 0.1%; −25.7–26.0%). Conclusion: Our findings suggest that MPR-based diameter measurement and the semiautomated perpendicular area minimal caliber computation methods cannot be used interchangeably for the quantification of ICA steno-occlusive disease.